Diversifikasi Daging Analog Berbasis Nabati: Potensi dan Tantangan Sumber Daya Perikanan Sebagai Bahan Baku Alternatif - Annisa Rizki Nurhasyimi; Annur Ahadi Abdillah; Annadiyah Latinsani; Ajeng Pramudita Anggraeni; Domas Patria; Jenshinn Lin (Universitas Mataram, 2026)
Growing public awareness of health, animal welfare, and environmental sustainability, lead to significant increase in demand for healthy and sustainable nutritious food segment. Plant-based meat analog (PBMA) has been development as alternative food ingredients that are in accordance with the current demands of the world community. However, currently raw materials of PBMA is still dominated from terrestrial plants which have limitations in terms of sustainability, land requirements, and specific nutritional profiles. These circumstances highlight the urgent need to diversify the raw material of PBMA and require further investigation. This paper focuses on potential and challenge of fishery resources as meat analog’s raw material alternative. Fishery resources emerge as promising alternative source offering sustainability and high quality nutrient values. Microalgae are a promising source, rich in protein, essential fatty acids, providing vitamins, minerals, and offering various bioactive compounds with health benefits and potentially improve the quality of meat analog. Hydrocolloids derived from algae such as carrageenan and alginate act as thickening, gelling, and stabilizing agents which improve the overall structure and texture of PBMA. Amino acid and natural pigment in algae enhance sensory acceptance of PBMA by masking undesirable taste and mimicking meat like color. This review will be helpful in highlighting the potential fishery resources in attempt to diversify material sources for PBMA.